2017
DOI: 10.1007/s00170-017-0839-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser powder-bed fusion of Inconel 718 to manufacture turbine blades

Abstract: In the frame of additive manufacturing of metals, laser powder-bed fusion is investigated in this paper as an advanced industrial prototyping tool to manufacture Inconel 718 turbine blades at a predesign stage before flow production. Expediting of the evaluation of any upgrade to the part is aimed. To this purpose, possible anisotropy of manufacturing is preliminarily investigated via tensile testing at room and elevated temperature as a function of the sloping angle with the building plate; the normalized str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Mower et al [13] also observed this typical microstructure in AlSi10Mg. For the mentioned materials, Lewandowski et al [10] described a similar tensile and 0.2% yield stress of AM-materials compared to conventionally manufactured materials and an anisotropic behavior of the AM-materials with regard to their building direction, which is in accordance to the observations of References [11,13,15,[17][18][19]. In these investigations, the Horizontal building direction, in which layer planes are perpendicular to the load axis, showed higher values compared to the vertically built specimens.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Mower et al [13] also observed this typical microstructure in AlSi10Mg. For the mentioned materials, Lewandowski et al [10] described a similar tensile and 0.2% yield stress of AM-materials compared to conventionally manufactured materials and an anisotropic behavior of the AM-materials with regard to their building direction, which is in accordance to the observations of References [11,13,15,[17][18][19]. In these investigations, the Horizontal building direction, in which layer planes are perpendicular to the load axis, showed higher values compared to the vertically built specimens.…”
Section: Introductionsupporting
confidence: 75%
“…Investigations of the microstructure and monotonic properties of the AM-materials are available in a large quantity. Microstructural investigations of Mower et al [13], Yasa et al [14], and Casati et al [15] on selective laser melted austenitic stainless steel AISI 316L showed an elongation of grains along the building direction and visibility of the layer boundaries in light optical micrographs (LOMs), which is in accordance to the investigations of Brandl et al [16] on laser deposition welded Ti6Al4V, Caiazzo et al on laser powder bed fused Inconel 718 [17], and Bauer et al [18] on the selective laser melted nickel based superalloy Haynes230 ® . Mower et al [13] also observed this typical microstructure in AlSi10Mg.…”
Section: Introductionsupporting
confidence: 73%
“…In the last few years, the use of components produced through additive manufacturing (AM) processes is rapidly growing in many industrial applications. AM parts are currently employed in applications subjected to static loads at room and high temperature [1,2], such as brackets [3], medical devices [4], or heat exchangers [5]; however, their use is still limited for applications subjected to fatigue loads [6,7]. Among the employed alloys, the ones belonging to the Al-Si system are drawing considerable interest thanks to their good mechanical properties and low density.…”
Section: Introductionmentioning
confidence: 99%
“…As regarding the output of the process, the resulting mechanical properties and the surface quality are of main concern. Indeed, it has been shown that the porosity, in terms of both amount [11] and size [12] of pores, is crucial for any process involving the laser beam [13], since an effect is played on the ultimate tensile strength and the overall hardness [7,8]; interestingly, a proper selection of the levels of the governing factors is the key to prevent possible anisotropy of the mechanical properties [14].…”
Section: Introductionmentioning
confidence: 99%